FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMBELI PAKAN TERNAK DI MAMMINASATA POULTRY SHOP (PS) - Iin Aprianty; Nugraha, Angga; Armayani M (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
The purpose of this study is to ascertain the impact of feed quality, price, promotion and location factors on consumer decisions to buy animal feed at Mamminasata Poultry Shop (PSA quantitative descriptive method was used for the research which included 55 respondents as a sample. The date was collected using the questionnaire method and check information used was multiple linear regression analysis with the help of SPSS 16.0 for windows. The results of this study show that the value of product quality coefficient (X1) is 0.0017, price (X2) is 0.002, promotion (X3) is 0.283 and location (X4) is 0.886. So it can be concluded that partially the product feed factor (X1) and price (X2) have a significant effect (P<0.05) on consumer decisions while promotional factors (X3) and location (X4) do not have a significant effect (P>0.05) on consumer decisions to buy animal feed. While the results of simultaneous test (F) showed that the Fcalculate value qas 4.809 with a significant level of 0.05 and the Ftable value was 2.786. Therefore, it is concluded that product feed (X1), price (X2), promotion (X3) and location (X4) have important influence on consumers decisions to buy animal feed